INNOVATIVE AND SUSTAINABLE ENTREPRENEURSHIP BASED ON INDUSTRY 5.0. EXPECTED BEST PRACTICES, INSIGHTS, AND PATHWAYS - Adrian PETRE (Business Excellence and Management)
Industry 5.0 highlights the need for synergy between digital technologies and human factors, to meet sustainability objectives and resilience within modern production systems. The general objective of this paper is to generate a representation of the research conducted so far on the topic of Industry 5.0, intending to ultimately understand whether researchers' perspectives indicate the capability of Industry 5.0 to support innovative and sustainable entrepreneurship, as well as to see the most representative application areas and the main boosters. The research methodology used is mainly based on bibliometric analysis. The general results indicate, first of all, that sustainability is one of the main insights in scientific research on the topic of Industry 5.0. On the other hand, advanced digital technologies, such as blockchain, digital twins, and artificial intelligence, are the main enablers of the new industrial revolution, and the areas in which they can be implemented are diverse. Finally, we highlight as limitations of this work the fact that the data were taken from a single database, as well as the reduced number of search criteria. As a follow-up to this work, potential future research is proposed, namely identifying the most representative enablers of Industry 5.0 depending on the implementation sector.